From Ritual to Consensus: Local Traditions as Mechanisms of Interfaith Harmony in Toraja, Indonesia - Jamal, Muh.; Wulandari, Taat; Nurhayati, Nurhayati; Irnawati, Irnawati (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2025)
This study investigates the role of Rambu Solo funeral rituals and Tongkonan ancestral houses in fostering interfaith harmony and social cohesion in Rembon, Tana Toraja, Indonesia. The research aims to explain how these traditions, beyond their symbolic functions, operate as practical mechanisms for conflict resolution and community solidarity in a highly plural society. This focus is crucial given Indonesia’s recurring challenges in managing religious diversity, where pluralism, if not effectively governed, can lead to social tension and communal conflict. A qualitative case study design was employed, drawing on in-depth interviews with traditional leaders, religious figures, and community members, complemented by participant observation and document analysis. Data were analyzed using thematic analysis to uncover the mechanisms, values, and processes embedded in Rambu Solo and Tongkonan. The findings reveal that Rambu Solo serves as a site of interfaith cooperation through collective participation in rituals, while Tongkonan provides a deliberative forum for consensus-building on social and religious issues. The implications suggest that Toraja traditions can serve as models for multicultural policy and practice, particularly in promoting local wisdom as instruments of peacebuilding. Adaptive strategies, including simplifying ritual obligations, integrating cultural values into education, and fostering interfaith dialogue between adat and religious leaders, are recommended to sustain harmony. The originality of this research lies in its demonstration that interfaith harmony emerges not only from doctrinal ideals or abstract principles but from living cultural institutions that embed pluralism into daily practices. By bridging Durkheim’s concept of collective consciousness and Weber’s theory of communal solidarity with empirical evidence from Toraja, this study contributes a distinctive model of sustainable pluralism rooted in indigenous traditions.